PRODUCTION ANALYSIS OF SMALLHOLDER OIL PALM ON PEATLAND AND DRYLAND IN RAWA BANGUN VILLAGE - Saputra, Dandi; Yuristia, Rahmi; Cahyadinata, Indra; Hayati, Nur Qomarian (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2025)
Oil palm is one of the commodities that plays a vital role in the Indonesian economy, especially in Bengkulu Province. Mukomuko District, Rawa Bangun Village, has oil palm plantations on peatland and dryland. This study aims to analyze production, productivity, and factors affecting smallholder oil palm production on peatland and dryland. Respondents totalled 84 oil palm farmers, determined by the Slovin method and Proportionate Stratified Random Sampling to divide peatland and dryland respondents. Production factors were analyzed using the Cobb-Douglas model. The results showed that the average production was 65,038 kg per year, and the average productivity was 21,967 kg per hectare per year in dryland, higher than in peatland. Factors of oil palm production show that land area, number of plants, and fertilizer significantly positively affect oil palm production in both types of land. Meanwhile, labour, pesticides, and plant age have no significant effect and tend to hurt oil palm production in both types of land.